Perilaku Konsumerisme Pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Sumatera Utara Tahun 2017-2022 - Septiani, Ayu (UIN Sumatera Utara, 2025)
Understanding the philosophy of consumerism has given birth to growth mania and megalomania in people's lives, especially in students. This has implications for two things, namely: the existence of moderate consumption behavior among students or high mass consumptions and wasteful consumption caused by the logical consequences of the development of the consumer movement that cannot catch up with the development of consumer desires and tastes that tend to be excessive and wasteful. Conversely, the desire for greater production in producers is also uncontrollable. Through data analysis that has been done, this study concludes that; 1) Students of the Faculty of Economics and Business UMSU Medan have a relatively high desire to consume, but the students of the Faculty of Economics and Business UMSU Medan can still maintain their achievement index on campus and not a few of them make the campus proud by winning competitions at the provincial, national and international levels. 2) Factors that cause consumptive behavior of students of the Faculty of Economics and Business UMSU Medan come from two factors, namely internal factors and external factors. Internal factors, consisting of; motivation and lifestyle. While external factors consist of; Advertising and self-identification models. 3) Consumptive behavior in students of the Faculty of Economics and Business UMSU Medan can be classified in the group of 'high mass consumptions' because they buy an item with indicators of 'prestige' and 'trend'.